PWE-111 Higher Red Blood Cell Methotrexate Polyglutamates Correlate With Increased Disease Activity, And Are Useful In Assessing Adherence. (9th June 2014) - Fong, S; Ward, MG; Nasr, I; Goel, RM; Patel, KV; Ray, S; Arenas Hernandez, M; Anderson, SA; Marinaki, T; Sanderson, JD; Irving, PM
Abstract : Introduction: Methotrexate (MTX) is commonly used in patients with inflammatory bowel disease (IBD). Within red blood cells (RBC), MTX is activated by sequential addition of glutamic acid residues to form polyglutamates (MTXPG 1–5 ). In rheumatoid arthritis, low [MTXPG] has been associated with active disease, whereas other studies have demonstrated an inverse relationship, including the only published data in IBD. The aim of this study was to determine if RBC [MTXPG] reflect clinical response in IBD patients and whether they are useful in assessing adherence. Methods: This was a single-centre, retrospective pilot study of 21 IBD patients treated with weekly MTX. RBC MTXPG1–5 was measured using high-performance liquid chromatography. Clinical status (active disease or remission) was assessed by 2 IBD physicians blinded to [MTXPG], using a combination of prospectively recorded clinical activity indices (Simple Colitis Activity Index, Harvey Bradshaw Index), endoscopy, faecal calprotectin and C reactive protein (CRP). Pearson correlation coefficient, r was calculated to assess the relationship between MTX dose and [MTXPG]. Association between [MTXPG] and clinical response was analysed with unpaired t-test. Results: 4/21(22%) patients (3 of whom admitted non-adherence) had undetectable MTXPGs and were excluded from further analysis. MTXPG2–4 were detected in all adherent patients. PG3 was the predominant polyglutamate accounting for a mean of 43% of total MTXPG. A linear relationship between dose of MTX and PG1–5 was observed. 12/21(57%) patients were assessed as having active disease. No significant difference in mean [MTXPGn ] was observed between those with active disease and remission. For each MTXPGn, a non-significant trend towards a higher concentration was observed in patients with active disease. Conclusion: In this study, the largest to date in IBD, measuring RBC MTXPG was useful in assessing adherence to MTX. A trend towards higher PG concentrations was associated with active disease confirming the findings in the only other study in IBD. Whether this is confounded by higher doses being used in patients with more active disease warrants further study in larger, prospective trials. Reference: Disclosure of Interest: None Declared.